The Assistance of Social Harmony Character of Children at Taman Pendidikan Al-Quran (TPA) Ar-Rahman East Metro City - Aisyah Khumairo; Oom Yomi Romlah (Yayasan Payungi Smart Madani, 2021)
The emergence of social conflicts with religious backgrounds such as blasphemy, destruction of houses of worship, hate speech on social media and mutual discredit between one congregation and another, or one congregation with another congregation. The conflict, if examined, is actually rooted in a failure to have a dialogue between religious understanding and social realities in a diverse, plural and multicultural society. So from these problems that the character of harmony for the general public is very important in the midst of daily life activities, considering that the diversity of society often causes various kinds of conflict problems, both between individuals and between groups with each other. The character development of children's harmony from an early age is an activity that is quite effective as a transfer of value, so this is deemed very necessary to be done as an alternative step in fostering the character of children's social harmony in the Tejoagung Metro Timur environment. The purpose of the social harmony character development activity is to provide knowledge and understanding regarding the importance of harmonious character values, assist children's habituation in implementing the harmony character and provide capacity building and quality strengthening for TPA teachers. This activity was carried out for the children of the Al-Qur'an Ar-Rahman Tejoagung Education Park in Metro City, the main activity was coaching by socializing using various strategies including coordination with TPA teachers, socialization of harmony values to teachers and students, visualization of images. religious multicultural images and learning methods using habituation, demonstrations, lectures, role models and games. The development of the character of harmony goes quite smoothly and has quite an impact on the students and teachers because it provides knowledge and understanding regarding the importance of the values of the character of harmony, children and teachers can implement the character of harmony in their daily lives Keywords: Social Harmony Character, Social Harmony, Assistance Social Character